2017
DOI: 10.5194/bg-2017-82
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Carbon and nutrient export regimes from headwater catchments to downstream reaches

Abstract: <p><strong>Abstract.</strong> Excessive amounts of nutrients and dissolved organic matter in freshwater bodies affect aquatic ecosystems. In this study, the spatial and temporal variability in nitrate (NO<sub>3</sub>), dissolved organic carbon (DOC) and soluble reactive phosphorus (SRP) was analyzed in the Selke (Germany) river continuum from headwaters draining 1–3 km<sup>2</sup> catch… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 29 publications
5
23
0
Order By: Relevance
“…In contrast, PO 4 3− variability was high (CV C 50–213%) and the CV C /CV Q ratio was chemodynamic at the mid flume and did not show a chemostatic trend at the upper flume. Higher variability in phosphorus (TP, PO 4 3− ) has also been observed by Thompson et al (), Musolff et al (), Dupas et al (), and Moatar et al (), and this variability could be due to threshold driven variability of sediment‐bound P, biological mediation, or to high rates of reactivity in streams being stronger controlling factors on concentration than discharge.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In contrast, PO 4 3− variability was high (CV C 50–213%) and the CV C /CV Q ratio was chemodynamic at the mid flume and did not show a chemostatic trend at the upper flume. Higher variability in phosphorus (TP, PO 4 3− ) has also been observed by Thompson et al (), Musolff et al (), Dupas et al (), and Moatar et al (), and this variability could be due to threshold driven variability of sediment‐bound P, biological mediation, or to high rates of reactivity in streams being stronger controlling factors on concentration than discharge.…”
Section: Discussionsupporting
confidence: 51%
“…Recently, C‐Q relationships have been analysed across a wide range of watersheds with differing catchment areas, climate conditions, lithologies, land covers, and land management methods (e.g., Basu et al, ; Burns, Boyer, Elliott, & Kendall, ; Dupas et al, ; Godsey et al, ; Moatar et al, ; Musolff et al, ; Thomas et al, ). The C‐Q relationships for many solutes varied across these studies, with Godsey et al (), Basu et al (), and Thomas et al () concluding that chemostatic patterns dominated parent material weathering elements such as Si, Na + , Mg 2+ , and Ca 2+ (Godsey et al, ), and vegetation‐limiting nutrients, such as NO 3 − and PO 4 3− , in agricultural watersheds (Basu et al, ; Thomas et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal variability in NNO3 concentrations at the two upper stations represents mainly the nitrate behavior in natural forest‐dominated areas, which has high interflow concentrations and extremely low baseflow concentrations. Due to the impermeable geological property, a shallow and flashier flow pathway is developed in the upper Selke (Dupas et al, ). The fertilizers and plant residues added to the upper arable lands and forests, respectively, increased NNO3 concentrations of soil moisture, but not of deeper groundwater.…”
Section: Discussionmentioning
confidence: 99%
“…The mHM‐Nitrate model provided detailed spatial information (e.g., spatially resolved nitrate terrestrial concentrations and fluxes) that is within reasonable ranges. Therefore, it offers promising opportunities for further evaluation of nutrient transport and removal processes spatiotemporally, for instance, to support future studies that target spatial agricultural mitigation measures (Hashemi et al, )and interactions between terrestrial and in‐stream processes (Dupas et al, ). Further validation of the new model needs to be done by cross validating for catchments that differ in natural conditions and scales.…”
Section: Discussionmentioning
confidence: 99%
“…The long‐term evolution of a catchment's water quality under changing external forcings, termed hereafter trajectory, does affect not only mean annual concentrations and fluxes but also intraannual variations. Seasonal variations in nutrient concentrations are often interpreted in terms of (i) dominant point versus diffuse sources (Jarvie et al, ; Withers et al, ); (ii) spatial distribution of nutrient sources in catchment, vertically (Abbott et al, ; Dupas et al, ; Musolff et al, ) or laterally (Aubert et al, ; Musolff et al, ); and (iii) temperature‐dependent release and retention mechanisms, within soils (Aubert et al, ; Dupas, Musolff, et al, ) or the river network (Mulholland et al, ; Rode et al, ). Worrall et al () observed that different components of the Thames nitrate time series (e.g., annual maxima and minima) had different responses to land use and climate drivers, and that the amplitude and phase of seasonal variations varied over a 130‐year period.…”
Section: Introductionmentioning
confidence: 99%